Carbon Cloth Decorated with MoS2 Microflowers as Flexible Binder‐Free Anodes for Lithium and Sodium Storage. Issue 5 (17th April 2019) - Kang, Jinwei; Feng, Huagui; Huang, Ping; Su, Qingmei; Dong, Shijia; Jiao, Weicheng; Chen, Xiaojuan; Du, Gaohui; Yu, Yuan; Xu, Bingshe
Abstract : Herein, a hierarchical architecture for high‐performance flexible lithium/sodium‐ion batteries (LIBs/SIBs) is reported, which comprises the interconnected carbon fiber cloth network (CC) decorated with MoS2 microflowers assembled by ultrathin MoS2 nanosheets (MoS2 /CC) through an in situ hydrothermal method and a subsequent calcination treatment. When used as a flexible binder‐free anode, the MoS2 /CC electrode shows an amazing cyclicality and a high reversible capacity for both lithium and sodium storages. As for LIBs, the MoS2 /CC composite delivers a high specific capacity of 1263 mAh g −1 after cycled for 100 cycles at 0.1 A g −1 . A rate capacity of 838 mAh g −1 can be obtained at 2 A g −1 after 100 cycles. As for SIBs, a reversible capacity of 515 mAh g −1 can be retained after 100 cycles at 0.1 A g −1 . The enhanced electrochemical properties of MoS2 /CC can be attributed to the following three synergic effects: 1) the carbon network offers an amazing conductivity environment without any binder or additive; 2) the sheet‐like structure of MoS2 provides the short Li ions diffusion path and can accommodate stress during cyclings; and 3) the 3D architecture ensures the well‐preserved structural integrity. The above results show that the MoS2 /CC composite holds great promise as a flexible anode for practical applications in next‐generation LIBs and SIBs. Abstract : The 3D MoS2 /carbon fiber cloth network (CC) hierarchical architecture is fabricated by a hydrothermal method. The MoS2 /carbon cloth (CC) composite can be used as a flexible binder‐free anode without binders or additives, and the MoS2 /CC electrode manifests amazing cyclicality and high reversible capacity for both lithium and sodium storages. The unique electrochemical performances can be ascribed to the unique structure of the 3D MoS2 /carbon cloth (CC) hierarchical architecture.